Quantification of vincristine and tariquidar by liquid chromatography‐tandem mass spectrometry in mouse whole blood using volumetric absorptive microsampling for pharmacokinetic applications. Issue 14 (20th May 2022) - Rosser, Sebastian P. A.; Atkinson, Caroline; Nath, Christa E.; Fletcher, Jamie I.
Abstract : A liquid chromatography‐tandem mass spectrometry method was developed and validated for the simultaneous quantification of vincristine and tariquidar in 10 μL of mouse whole blood using volumetric absorptive microsampling devices. Samples were extracted from the devices and quantified against calibrators prepared in a human blood plasma matrix. Separation of vincristine and tariquidar was achieved using a Shimpack XR ODS III C18 stationary phase and H2 O and methanol mobile phase solvents containing 0.1% formic acid, running a gradient elution at a flow rate of 0.2 mL/min over 6.0 min. The method was linear up to 1200 ng/mL ( R 2 > 0.99 for both analytes), with calibrator accuracy within ± 15% of the nominal concentrations and analyte coefficient of variance <15% for both vincristine and tariquidar. Pharmacokinetic assessment of both analytes was successfully applied in mice as both single‐agent therapy and combination therapy over a 24‐h period, and a 2.3‐fold increase in vincristine drug exposure was observed in combination with tariquidar. This study validates the use of this approach for longitudinal analysis of drug exposure in animal studies.